2019
DOI: 10.1002/ajhb.23333
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle mass in female athletes: The average and the extremes

Abstract: Objectives To examine the absolute and relative skeletal muscle mass (SM) in female athletes and to discuss the potential upper limit of whole‐body muscle mass between large sized female and male athletes. Methods Forty‐five female athletes and forty‐five recreationally active females (control) had muscle thickness measured by ultrasound at nine sites on the anterior and posterior aspects of the body. SM was estimated from an ultrasound‐derived prediction equation. Body fat percentage and fat‐free mass (FFM) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…For example, a cross‐sectional study reported approximately 75% greater whole‐body (ie, trunk plus four limbs) muscle mass when compared between resistance‐trained male athletes and recreationally active males (Abe et al, 2018). This difference was also evident when comparing resistance‐trained female athletes and recreationally active females (Abe et al, 2020). Similarly, muscular strength as determined by single joint (ie, elbow extension, knee extension, and ankle plantarflexion) tasks and multi‐joint (ie, squat and bench press) tasks was ~82% higher in resistance‐trained males than untrained males (Sale & MacDougall, 1984; Shimano et al, 2006).…”
Section: Introductionmentioning
confidence: 91%
“…For example, a cross‐sectional study reported approximately 75% greater whole‐body (ie, trunk plus four limbs) muscle mass when compared between resistance‐trained male athletes and recreationally active males (Abe et al, 2018). This difference was also evident when comparing resistance‐trained female athletes and recreationally active females (Abe et al, 2020). Similarly, muscular strength as determined by single joint (ie, elbow extension, knee extension, and ankle plantarflexion) tasks and multi‐joint (ie, squat and bench press) tasks was ~82% higher in resistance‐trained males than untrained males (Sale & MacDougall, 1984; Shimano et al, 2006).…”
Section: Introductionmentioning
confidence: 91%
“…Muscle thickness (MT) and subcutaneous adipose tissue thickness (SAT) were measured by B‐mode ultrasound (Logiq e, GE, Firfield, CT and SSD‐500, Aloka, Tokyo, Japan) at nine sites on the right side of the body as described previously (Abe, Buckner, Dankel, et al, 2018; Abe, Wong, et al, 2020). This measurement was carried out at least 24 hours after the last their training session.…”
Section: Methodsmentioning
confidence: 99%
“…This is mainly due to the fat‐free component of adipose tissue being included in the measurement of FFM when estimated by underwater weighing methods. The large‐sized (>100 kg body mass) female athletes had approximately 10 kg fat‐free adipose tissue (50‐60 kg fat mass), which corresponds to about 10% to 15% of FFM (Abe, Wong, et al, 2020). It is desirable to eliminate the influence of the fat‐free component of adipose tissue to remove these effects from FFM or is desirable to estimate SM of the body in athletes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, a study reported that there was an inverse correlation ( r = −0.449) between body fat percentage and functional movement screen scores among college football players (Nicolozakes, Schneider, Roewer, Borchers, & Hewett, 2018). Further, there were inverse correlations between the percentage of body fat and high‐speed movement performance in sprint and distance running (Abe et al, 2020; Alvero‐Cruz et al, 2019; Herrmann et al, 2019), cycling (Schabort, Killian, St Clair Gibson, Hawley, & Noakes, 2000) and soccer matches (Radziminski, Szwarc, Padron‐Cabo, & Jastrzebski, 2019).…”
Section: Introductionmentioning
confidence: 99%